Remembering the Holocaust: A Reading of Howard Jacobson’s Kalooki Nights - Devi, Smita (International Journal of Advanced Science and Technology, 2020)
Journey of the Jews have never been so smooth. Since medieval period till today they have been facing maltreatment. However, holocaust displays the height of inhumanity with mass-extermination of the Jews. Jews need to suffer enormous brutality during the reign of Hitler. Though, it has been assumed that holocaust ends with Nazis yet it still persists in the minds of Jews. HowardJacobson documents a contemporary outlook to the whole idea of holocaust by comparing with Jewishness. Jacobson portrays the dreadful journey of Jews who needs to carry the burden of both holocaust, their culture and religion. Current study aims to explore this journey of Jews which seizes their concord, existenceand their personal life. The study will also analyse the traumas of holocaust and their impact on modern day Jewish life.